The Kinetic Family Drawing Test for Evaluating Interpersonal Dynamics in Families: A Case Study (Medico Legal Update, 2020)
The purpose of this study is to evaluate interpersonal dynamics through Kinetic Family Drawing (KFD).Art Based Therapy (ABT) can be used in situations where talk therapies and counselling skills are leasteffective. It is especially helpful for people in crisis and those who are experiencing extreme psychologicalstates. This case study has employed The Kinetic Family Drawing (KFD) to diagnose and treat 62 years oldmarried woman with complaints of sadness, uncertainty & fear. This ABT program comprised of 3 sessionsin which the Burns and Kaufman’s (1972) Kinetic Family Drawing (KFD) was used4. In each session theclient was made to draw a picture on a sheet of paper (8.5” x 11”) 4. The picture drawn by the client wassubsequently analysed using focal points and the results were discussed with the client. The outcome of thepresent study helped the client to get insight into her problem and regain her self-confidence and improverelationship with her family members.